Rethinking sales management : a strategic guide for practitioners - Rogers, Beth, 1957- (Chichester, England ; Hoboken, NJ : John Wiley & Sons, 2007)
Until recently, sales managers received no specific training for their jobs. However, selling has become more complex with the emergence of regulations and more sophisticated customers. Sales managers need to inspire and achieve sales results by managing teams of professionals and other resources. To do so, they need guidance on dealing with issues that arise in these broader aspects of their role. This concise guide for sales managers is based on a well-known sales management technique called the 'customer portfolio matrix'. Beth Rogers weaves her version of this throughout, enabling sales ma.
Strategy -- The big picture -- The purchaser's view -- The B2B relationship box -- Using the relationship development box -- Strategic relationships -- Prospective relationships -- Tactical relationships : the power of low touch -- Cooperative relationships -- The end of relationships -- Strategic focus for the 21st-century sales management -- Reputation management -- Working with marketing -- Leadership -- Process management.
Includes bibliographical references (pages 267-279) and index.
Print version record.
John Wiley and Sons
Keywords: Sales management; Ventes -- Gestion; BUSINESS & ECONOMICS -- Sales & Selling -- Management; Sales management